THE ROLE OF ISLAMIC FINTECH IN PROMOTING FINANCIAL INCLUSION IN THE DIGITAL ECONOMY ERA - Afrizal, Afrizal (MSJ : Majority Science Journal, 2025)
This study aims to analyze the effect of Islamic fintech adoption on financial inclusion in the digital economy era and to examine the moderating role of sharia financial literacy. A quantitative survey approach was employed using an online questionnaire distributed to users and potential users of Islamic fintech services in Indonesia. Purposive sampling resulted in 241 valid responses. Data were analyzed using hierarchical multiple regression. The findings indicate that Islamic fintech adoption has a positive and significant effect on financial inclusion. Sharia financial literacy also shows a positive and significant impact on financial inclusion. Moreover, sharia financial literacy functions as a moderating variable that strengthens the relationship between Islamic fintech adoption and financial inclusion. These results affirm that Islamic fintech serves as a strategic instrument for broadening financial access; however, its effectiveness is strongly influenced by the level of public understanding of sharia financial principles. Therefore, enhancing sharia financial literacy and developing an inclusive digital ecosystem are crucial in promoting more equitable financial participation.